The Roles of Collaborative Dialogue in Enhancing Written Corrective Feedback Efficacy - Asiah, Kassim; Ng, Lee Luan (MELTA, 2014)
This paper discusses findings from a qualitative investigation to identify factors in relation to language-related episodes (LREs) that influence the uptake and retention in the accurate use of subject-verb agreement and prepositions resulting from indirect focused and indirect unfocused written corrective feedback. In relation to these identified factors, the roles of collaborative dialogue were determined through the analyses of the LREs and the interviews with selected participants. The participants in the study who received either focused or unfocused indirect corrective feedback for their written work were required to revise their work collaboratively during the pair talk. Findings from the analyses of the two data sources suggest that collaborative dialogue played a crucial role in enhancing the corrective feedback efficacy in facilitating participants’ language learning development. Primarily, collaborative dialogue enhanced learners’ focus towards ungrammatical uses in written work. Working collaboratively also provided learners with means to extensively deliberate over the corrections, which led to insightful reflections on their existing linguistic knowledge in response to the corrective feedback that they received for their written work.